INNOVATIVE CHANGES IN FINANCIAL AND TAX SYSTEMS IN THE CONDITIONS OF DIGITAL TRANSFORMATION - Pochenchuk, Galyna; Manzhura, Oleksandr; Kraus, Nataliia (My University, 2022)
The purpose of the research is to present the features of innovative changes in financial and tax systems in terms of digital transformation as a foundation to build a new quality of economic system in terms of virtual mobility and financial technologies that change business in the direction of its electronic direction. The object of the scientific research is the process of digitizing innovative changes in financial and tax systems in terms of virtual mobility, which has every chance to become a decisive step in implementing digital development strategy of Ukraine through the development of digital financial instruments, digitized financial development institutions, smart services and efficient defining a new quality of management of financial and tax systems. Methodology. By relying on comparative-retrospective analysis, synthesis, and system method, the digitalization of innovative changes of financial and tax systems is investigated. It determines the new quality and format of work of financial development institutions in the times of deepening virtual mobility. Comparative analysis was used to study the content of regulatory and supervisory financial technologies, namely: RegTech, SupTech; the functions of financial system that reveal its role are indicated. The result of the article. Factors contributing to the development of financial system are presented; the authors give their vision of the content of non-financial companies that provide traditional financial services in virtual reality. The content of some innovative and digital changes in the Ukrainian tax system has been identi-fied and disclosed. Practical implications. It is argued that key innovative changes that need to be addressed in the context of reforming and digital transformation of financial system have been revealed. Factors contributing to the development of financial system are presented. The peculiarities of digital initiatives that take place in the taxation system are indicated. Value/originality. In order to timely inform taxpayers in the media and on the web portal of the tax service, it is proposed to systematically covers main issues regarding the procedure for filing tax returns, categories of taxpayers required to file reports, deadlines for such reporting, list of costs included as part of tax rebate. Payer Service Center should implement this awareness. Author’s vision of the content of practical work of non-financial companies providing traditional financial services in the conditions of virtual mobility is presented and thoroughly revealed
Keywords: innovative changes, digital financial technologies, financial system, digital transformation, digitalization of tax system